Evaluasi Perangkat Pembelajaran Daring dalam Menstimulus Enam Aspek Perkembangan Anak Usia Dini - Umahatun Fauziyah; Siti Masitoh; Sri Setyowati (Journal of Elementary School (JOES), 2022)
This study aims to improve the quality of teachers in the virtual teaching and learning process, through discussions related to the preparation of online RPPH to increase teacher creativity in choosing learning activities, and improve teacher skills in evaluating learning as improvement material for the preparation of online RPPH in Al Ummah Manyar Islamic Kindergarten. Gresik. The method in this study is qualitative with observation and interview data collection techniques, using fourteen subjects to be observed in a relatively long time, namely six months. Al Ummah Integrated Islamic Kindergarten teachers have also used media and learning resources that are in accordance with the play while learning approach. In the development of activity planning, it is still not visible, the results of interviews with parents also stated that the slogans or jargon used by the teacher lacked innovation, and the theme songs were less varied. So it can be concluded that by participating in various trainings and also being able to conduct comparative studies to other schools related to the management of online learning can increase the creativity of teachers in designing learning activities.. Keywords: Evaluation, Device, Online, Development